2018
DOI: 10.15277/bjd.2018.170
|View full text |Cite
|
Sign up to set email alerts
|

Driving and diabetes: are the changes in the European Union licensing regulations fit for purpose?

Abstract: Driving is an important everyday activity for many people with diabetes, which is designated a prospective disability as it may impair driving performance as it progresses in severity. In effect, the principal threat to driving performance is hypoglycaemia associated with insulin therapy. Regular assessment of medical fitness to drive is undertaken to identify drivers with diabetes who are at greatest risk of experiencing motor vehicle accidents. Many countries do not restrict the licensing of drivers with ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Unawareness of hypoglycemia is indeed considered an important risk for drivers with diabetes, 11 however, discussed for car collision 1 . A possible reason for these discordant results might be that the definition and assessment of an impaired awareness of hypoglycemia are not consensual 16 . This phenomenon seems to be associated with repeated exposure to hypoglycemia, partly by modifying the counter-regulation response to a BG decrease 1,2,29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unawareness of hypoglycemia is indeed considered an important risk for drivers with diabetes, 11 however, discussed for car collision 1 . A possible reason for these discordant results might be that the definition and assessment of an impaired awareness of hypoglycemia are not consensual 16 . This phenomenon seems to be associated with repeated exposure to hypoglycemia, partly by modifying the counter-regulation response to a BG decrease 1,2,29 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that a nonnegligible proportion of insulin-treated drivers reported an episode of hypoglycemia behind the wheel in the past year and it may even have been underestimated if self-reported hypoglycemic events were omitted because of fears of losing one's driver's license, as already described. 16 The rates reported in the literature vary widely from 13.4 to 66% in questionnaire-based survey including both type 1 and type 2 diabetic patients. 15,[17][18][19] This broad range reflects firstly differences in populations in mean age, 17,19 proportion of male, 15,19 proportion of patient with type 1 diabetes, 15,18 and sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Sudden hypoglycaemia followed by unconsciousness is the most important concern when assessing the ability to drive, whereas the tendency is more pronounced in T2DM patients treated with insulin, sulfonylureas or glinides. 75 The reader is referred to specialised literature for more details. 75–77…”
Section: What To Target and How To Intervene In Cvd Patients With Diamentioning
confidence: 99%
“…The key changes were reviewed recently by Graveling and Frier. 21 These changes include stating ‘ inadequate awareness’ rather than ‘ impaired ’ hypoglycemia, reduction in the length of time of revocation of a driving license from 12 to 3 months, and restricting the relevance of severe hypoglycemia to waking hours. 21 Globally, there is a wide variation between different countries and regions in the statutory requirements and policies used to regulate and assess drivers with diabetes.…”
Section: Hypoglycemia Driving and Licensing Standardsmentioning
confidence: 99%